Crystal structure of dichlorido-bis(4-chlorophenyl-κC)-bis(triphenylarsine oxide-κO)tin(IV), C48H38As2Cl4O2Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open [Commercial Publisher], 2021)
C48H38As2Cl4O2Sn, monoclinic, P21/n (no. 14), a = 10.8019(1) Å, b = 14.6976(1) Å, c = 13.6266(1) Å, β = 90.983(1)°, V = 2163.07(3) Å3, Z = 2, Rgt(F) = 0.0199, wRref (F2) = 0.0514, T = 100 K.